Aprendendo a marchar: os desafios da gestão municipal do ensino fundamental e da superação do analfabetismo escolar. - Maia, Maurício Holanda (2006)
The present study reports an undertaking by the Municipal Administration of Education in the city of Sobral, State of Ceará, from 2001 to 2004, where, within a context of intense municipalization of elementary school teaching in Brazil and deterioration of the learning results of 4th graders, this municipality has successfully implemented a policy of literacy at the right age, which defines as its major goal having a 100 percent of the students from Sobral able to read and write by the age of seven. This study has been organized in three basic aspects. The first aspect deals with the statistics and analysis of relevant elements of the municipalization process of education, which took place in the country from 1995 on. The implementation of the educational policy adopted at the municipal level in Sobral is reported in the second aspect of this study, focusing the period ranging from 2001 to 2004, with particular emphasis on the external evaluations of reading and writing. The third and last aspect is one of reflection and synthesis, when the economical, political, social, and educational history of Brazil is taken into account, in order to understand the past and get a glimpse of the future. Last but not least, a question is proposed: which past and present factors allow us to understand how a society can grow without schools or schooling for all its members, as was the case in Brazil from the 30’s to the 80’s? Or to have schools and schooling in which there was no mastering of reading, the basic condition for wider and diverse learning, as happened in this country in the 90’s and the first half of this decade? We believe that the report of this experiment and its analysis can become an effective tool to strengthen the municipal administration of public education with the aim of overcoming the serious problems it still faces, among which, and with absolute priority, school illiteracy.